Barriers to thyroid cancer screening with ultrasound in patients with familial adenomatous polyposis. (7th March 2019) - Nagy, Celeste; Kelly, Zachary; Keilin, Steven; Willingham, Field; Chen, Amy
Abstract : Objectives/Hypothesis: To identify barriers to care in patients with familial adenomatous polyposis (FAP) that have not undergone ultrasound for thyroid cancer (TC) screening. Study Design: Case series and survey. Methods: A study was conducted examining referral patterns for thyroid ultrasound (TUS) in FAP patients for TC screening. Patients with FAP seen at our institution were identified using International Classification of Diseases, Ninth Revision and Tenth Revision codes. Chart review was performed for TUS and the results were recorded. Patients and healthcare providers were surveyed to determine barriers to TUS and opportunities for improvement. Results: Thirteen out of 35 patients surveyed (37%) were told by a healthcare provider that TUS was recommended for TC screening. The incidence for TC in FAP patients ranges from 15 to 12%, whereas the general population risk is 0.02% to 1%. In our series, one patient of 12 (8%) had TC. Barriers to care included poor patient education about the risk of TC in FAP and miscommunication among specialties for referral for TUS. Also, patients enrolled in a FAP registry have improved care, as they are more likely to undergo TUS than those not enrolled. Conclusions: FAP patients are at a higher risk of developing TC. Therefore, it is important for these patients to be informed and follow the recommended guideline to get a baseline TUS for screening as well as receive better patient education about the risk of TC and improved communication among specialties. Additionally, patients enrolled in a FAP registry are more likely to undergo ultrasound for TC screening, so there needs to be more centralized coordination for the multidisciplinary care of this disease. Level of Evidence: NA Laryngoscope, 129:2436–2441, 2019